Spatial pattern formation in chemical and biological systems - Maini, P; Painter, K; Chau, H (1997)
One of the central issues in developmental biology is the formation of spatial pattern in the embryo. A number of theories have been proposed to account for this phenomenon. The most widely studied is reaction diffusion theory, which proposes that a chemical pre-pattern is first set up due to a system of reacting and diffusing chemicals, and cells respond to this pre-pattern by differentiating accordingly. Such patterns, known as Turing structures, were first identified in chemical systems only recently. This article reviews the application of reaction diffusion theory to chemical systems and then considers a number of biological applications.